Examining the Determinants of User’s Satisfaction in Drinking Water Services: A Dual-Theoretical Perspective of Expectancy-Value and Service Quality Theory - Timalsina, Keshab Prasad; Adhikari, Bhaskar Chandra (International Research Journal of MMC, 2025)
This study investigates the determinants of customers' satisfaction with drinking water management services, namely user expectations, perceived value, service quality, gap analysis, and user awareness. Guided by Expectancy-Value Theory (EVT) and Service Quality Theory (SERVQUAL), the study employed a cross-sectional survey design using 399 users as respondents selected through stratified cluster sampling and data was gathered through Computer-Assisted Interviewing (CAI) with a structured interview schedule. The total sample and two categories of service providers, Consumer Committee and Drinking Water Board, were compared using regression analysis through structural equation modeling to determine the relationships among variables. The results showed that service quality had the largest and largest-scale positive effect on customer satisfaction in all groups, with standardized regression coefficients of 0.320 (p < 0.001) in total, 0.264 (p = 0.001) for the Consumer Committee, and 0.306 (p < 0.001) for the Drinking Water Board. Gap analysis found that only Drinking Water Board users showed a strong positive relationship between them (standardized β = 0.248, p = 0.002), indicating the precedence of expectation–performance congruence in larger institutions. User’s expectations and perceived value had a weak or insignificant impact on overall satisfaction, whereas user awareness had a moderate and significant positive impact among Drinking Water Board users (standardized β = 0.135, p = 0.027). The results indicate that while improving service quality remains the most effective way to enhance user satisfaction, addressing expectation gaps and enhancing user awareness become especially important in more complex service delivery systems. This study adds value to both academic theory and practical strategies aimed at improving user satisfaction within public water supply services.